Factibilidad para la creación de un parque temático de cacao (theobroma cacao) cantón Bolívar 2010 - Burbano Sánchez, Carmen María (2011)
The purpose of this research was to determine the feasibility of creating a cacao park theme in the Canton Bolivar, specifically at El Limon site, in order to promote the culture of Ecuador in cocoa, for which the respective studies were conducted in : market, technical, economic, financial and environmental analysis. For the analysis of supply and demand, a survey was applied to people in the cantons of Bolivar Tosagua, Chone and Junín, based on this study established the distribution of areas of the park's facilities including the necessary personnel, materials and equipment of each area, according to the flow and amount of people. The economic and financial viability was determined based on estimates of cash flow, NPV, IRR and payback period. Finally, the environmental impact was determined by estimating the level of construction and operational phase of the park. The market survey showed a 90% of potential demand. The technical study allowed us to establish the optimal size of the park facilities of 3389.9 m2. The economic and financial study revealed that the project is viable, the IRR reflects the 39% rate attractive to any investor, the investment is recover in a period of 2 years and 5 months. In the environmental strategies were proposed to mitigate, eliminate and control potential impacts to the environment. It concludes that the creation of a cacao park theme is feasible considering the results achieved during the development of the idea.